2017
DOI: 10.1200/jco.2017.35.15_suppl.e18014
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to oral therapies in metastatic castration resistance (m CRPC) prostate cancer patients: The ADOPTA study.

Abstract: e18014 Background: With the increasing use of oral anticancer treatments understanding adherence patterns and patient’s information about therapy has become critical. Enzalutamide (ENZ) and Abiraterone acetate (AA) are orally administered drugs approved for the treatment of mCRPC widely prescribed; however, scarce information is available about treatment compliance and patient’s information about these compounds. This study aims to evaluate the adherence to AA and ENZ and the patient’s drug knowledge in mCRPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Four prospective 48,51,66,71 and nine retrospective studies 6165,6770 reported adherence outcomes for patients receiving ARATs for mCRPC (Table 2). Three used self-reported measures as the main adherence outcome 66,71 and 10 employed observer-reported measures. 48,6165,6770…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four prospective 48,51,66,71 and nine retrospective studies 6165,6770 reported adherence outcomes for patients receiving ARATs for mCRPC (Table 2). Three used self-reported measures as the main adherence outcome 66,71 and 10 employed observer-reported measures. 48,6165,6770…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified a total of 694 records, resulting in a total of 16 eligible studies reporting results from assessment of adherence to oral therapies in prostate cancer patients (Preferred Reporting Items for Systematic Reviews and Meta-Analyses, Figure 1). In all, 13 observational studies assessed adherence and related measures exclusively in mCRPC patients (Table 2), 48,51,[61][62][63][64][65][66][67][68][69][70][71] while one phase III trial and two observational trials assessed adherence in advanced prostate cancer (Table 3). 14,53,72 Studies were mostly conducted in North America (n = 7) and Europe (n = 8) based on data from large national or provincial registries or hospital network databases (11), or smaller multi-or singlecenter analyses (5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer patients are also at risk of food–drug interactions, and serious patient education pitfalls in understanding treatment compliance have been identified [ 33 ]. On the other hand, use of complementary and alternative medicine (CAM) has increased in the last decade in both palliative and curative settings, with different reasons argued by patients for the use of these compounds [ 34 , 35 ].…”
Section: Safety Considerations In Oncological Patientsmentioning
confidence: 99%